Risk factors of coronary heart disease among male patients in Kuala Lumpur Hospital : a case-control study, 1995 - Anita Suleiman,; Md. Idris Mohd Nor, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Coronary heart disease is still the leading cause of mortality in Malaysia and also in other industrialized countries all over the world. Changes of human life style has been implicated as the cause of this disease. A case-control study has been conducted in Kuala Lumpur Hospital to identify the predictive factors for coronary heart disease in Kuala Lumpur population. Besides, this research is also geared to look for the relationship between coronary heart disease and other risk Factors including age, race, income, duration of education, hypertension, diabetes, body mass index, smoking, blood cholesterol and triglyceride and daily fat intake in the diet with hypothesis that coronary heart disease is associated to those risk factors mentioned. Respondents were male patients admitted to all classes of ward from December 1994 till Mach 1995 and fulfilled the inclusion criteria. Total or 102 respondents were recruited in this research in which 44 were cases diagnosed as coronary heart disease by the attending medical officer in charge and 58 were patients admitted with diagnosis other than coronary heart disease, hypertension or diabetes or other heart diseases acting as controls. The results are coronary heart disease is significantly associated with smoking (p<0.001 ), blood cholesterol (p<0.001) and body mass index (p<0.0 I) but not with other risk factors in univariate analysis. However, only smoking and blood cholesterol able to predict this disease in multivariate analysis. Odds ratio (Mantel-Haenszel) for smoking more than 20 sticks per day found to be 9.49 (confidence interval 95% 2.91,40.81) and 21.26 for high cholesterol level (confidence interval 95% 8.01,125.53).